Transit Oriented Development (TOD) for Early-Built Rail-Based Transit Stations: Possible or Plausible? - Yusfida Ayu, Abdullah; Khalid, Zanudin; Marlyana Azyyati, Marzukhi; Fatin Nabilah, Nawawi; Nor Baizura, Jamaluddin (Malaysia Institute of Planners, 2023)
Transit Oriented Development (TOD) embraces many principles, and is believed to be beneficial in tackling the issues of urban transportation. Some of the main dilemmas are urban accessibility, traffic congestion, and the efficacy of the public transportation system. In Malaysia, the TOD concept was introduced in 2005, much later after Calthorpe embarked on the idea. Rail-based public transport emerged much earlier in Malaysia to meet the demands for public transportation. To date, it is still debatable whether these transit stations deliver on the principles of TOD. Hence, to determine that, this study examined two transit stations that were developed way before the TOD concept was executed in the country. The aim was to evaluate the core areas of Subang Jaya Commuter Station and Tun Sambanthan Monorail Station, based on their components and features, in relation to TOD principles, and to examine the possibility of these early-built transit stations in becoming an ideal TOD. The study evaluated the land use components using the Case Study Method, together with the existence of several principles, namely “connectivity”, “facilities”, “safety” and “comfort”. Results indicated that both transit stations reflect some of the TOD measures, but these are not comprehensive throughout the 400m radius of the core areas. The stations have potential, but require a systematic approach to achieve TOD ideals since both areas are saturated with development, and making changes to land use may not be straightforward.